2000
DOI: 10.1046/j.1563-2571.2000.200102.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Psychotropic Drugs and Thyroid Hormone Metabolism an Overview

Abstract: Psychotropic drugs can influence synthesis and metabolism of thyroid hormones at different sites. Generally, lithium, tricyclic antidepressants and phenothiazines lead to a reduction in synthesis and/or metabolism of thyroid hormones. The induction of autoimmune thyroid disorders by lithium and phenothiazines has been proven in animal studies and possibly can also be found in humans. Antipsychotic drugs generally exert their therapeutic effects through a modulation of the monoaminergic and serotoninergic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It is known that lithium influences synthesis and/or metabolism of thyroid hormones at different sites. Ramschak-Schwarzer et al (37) have also noted inhibitions of T 3 and T 4 levels in the liver and kidney following extremely high doses of lithium feeding in rats. In the current study, lithium decreased liver and kidney T 3 and T 4 levels in acute (10 days) and chronic (25 days) treatments both in adult and aged rats.…”
Section: Discussionmentioning
confidence: 90%
“…It is known that lithium influences synthesis and/or metabolism of thyroid hormones at different sites. Ramschak-Schwarzer et al (37) have also noted inhibitions of T 3 and T 4 levels in the liver and kidney following extremely high doses of lithium feeding in rats. In the current study, lithium decreased liver and kidney T 3 and T 4 levels in acute (10 days) and chronic (25 days) treatments both in adult and aged rats.…”
Section: Discussionmentioning
confidence: 90%
“…The cause of these changes may be secondary to decreased synthesis of thyroid hormone or modulation of deiodinase enzymes. 311,312 In vitro studies and in vivo animal studies demonstrated that chlorpromazine induced a decrease in RAIU. 313,314 However, in humans, an increase in RAIU and a decrease in renal clearance of iodide were observed after 6 weeks of treatment with chlorpromazine and procyclidine.…”
Section: Desipraminementioning
confidence: 99%
“…In about 10% of patients maintained on lithium, output of triiodothyronine (T3) and thyroxine (T4) is impaired, owing in part to decreased end-organ sensitivity to TSH, possibly decreased thyroid uptake of iodine, less efficient release of synthesized T3 and T4 and their decreased coupling with thyroglobulin. [95,96] Some antidepressants, anticonvulsants and antipsychotics may also decrease thyroid function. [96][97][98][99][100][101] Other agents employed for mood-stabilizing effects, including carbamazepine, divalproex sodium and lamotrigine, are far less likely to affect thyroid functioning than lithium.…”
Section: Hypothyroidismmentioning
confidence: 99%
“…[95,96] Some antidepressants, anticonvulsants and antipsychotics may also decrease thyroid function. [96][97][98][99][100][101] Other agents employed for mood-stabilizing effects, including carbamazepine, divalproex sodium and lamotrigine, are far less likely to affect thyroid functioning than lithium. [99] However, carbamazepine and phenytoin can reduce binding to thyroidbinding globulin to increase circulating levels of free thyroid hormone, as well as increasing metabolic clearance of T4.…”
Section: Hypothyroidismmentioning
confidence: 99%